How Can We Improve Teacher’s Work Engagement? Based on Chinese Experiences - Zhang, Danhui; He, Jingwen; Fu, Dingmeng (Frontiers in Psychology, 2021)
Drawing on Self-Determination Theory, the current study analysed the relationship between teachers’ perceived autonomy support and work engagement while it also explored the mediating effect of basic psychological needs satisfaction and intrinsic motivation. The study investigated 520 elementary teachers in Beijing, and we found the following: (1) teachers in different groups reported diverse senses of perceived autonomy support, in that teachers with less teaching experience as well as those with a master's degree, have a higher score regarding the perceptions of teacher autonomy; and (2) teacher autonomy can affect work engagement not only in terms of the satisfaction of basic psychological needs but also by the chain of satisfaction of basic psychological needs and intrinsic motivation. Teachers with more autonomy support will have higher basic psychological needs satisfaction and stronger teaching motivation, which will further enhance their work engagement.